Coronary Stent Infection in Acute Double Valve Endocarditis - Filip Stembal, MD; Maria Bakaeen; Valentina Lara Erazo, MD; A. Michael Lincoff, MD; Steven M. Gordon, MD; Bo Xu, MD; Laura Young, MD; Marijan Koprivanac, MD, MS (JACC: Case Reports)
We present a patient with aortic and mitral valve endocarditis who presented with acute ST-segment elevation myocardial infarction. The patient underwent percutaneous coronary intervention, aspiration thrombectomy, and stent placement. A transthoracic echocardiogram subsequently revealed endocarditis. During surgery, an abscess was found around the stent and was surgically managed.